Pengaruh Harga, Lokasi, Kualitas Pelayanan & Kepuasan Konsumen Terhadap Keputusan Pembelian - ANAM, CHAIRUL, Muzakar Isa, SE, M.Si (2017)
This research is aimed to observe the influence of cost, location, service quality toward purchase and consumer satisfaction as mediation variables. The sample of this research is the consumer of Kopi Dara coffee shop which is about 93 respondents. The technique of collecting the data is used purposive sampling. While the method of analyzing the data is doubled linear regression alanysis test with T and F test, and determination coefficient (R2). In this research, the data is fulfilled for normal distribution. From the hypothesis test, the researcher found that cost and service quality influences toward the consumer, but the location does not influence toward consumer satisfaction. Both location and service quality influence towards the purchase, while the cost does not influence toward it. The consumer satisfaction can mediate between cost, location and service quality toward the purchase.